Presumptions of effective operation of diesel engines running on rme biodiesel. Research on kinetics of combustion of rme biodiesel - Lebedevas, Sergejus; Vaicekauskas, Andrius; Suškov, Pavel (Transport, 2007)
The results of experimental research on kinetics of fuel combustion of diesel engine A41are presented in the publication. The change of characteristics of indicated work (in‐cylinder pressure and temperature, period of induction, heat release and heat release rate) and fuel injection (fuel injection pressure, fuel injection phases) was determined in diesel engine running on RME biodiesel being compared to diesel fuel. The results of researches were used to explain experimentally determined changes of operational and ecological characteristics of diesel engine running on RME biodiesel. In addition, the reliability of diesel engine A41 running on RME biodiesel was evaluated. The presumptions of effective operation of diesel engines running on RME biodiesel were formulated. First Published Online: 27 Oct 2010